SANKSI TINDAKAN KEBIRI PERSPEKTIF TEORI PEMIDANAAN ISLAM (Telaah Kritis Terhadap Perppu Nomor 1 Tahun 2016) - Anta Rini Utami; Khairil Akbar; Nursiti Nursiti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This article will review the perspective of Islamic punishment theory on the sanctions for castration in Perppu 1/2016 which has now been enacted into law. Its derivative regulations in the form of Government Regulations have also been ratified. Using a conceptual and statutory approach, this article will answer and explain the question of how the castration sanction in the Perppu a quo according to Islamic criminal theory is descriptive-qualitative. Sanctions in Islamic crime against perpetrators of sexual crimes are a matter of jarimah and the sanctions are the authority of the authorities and are classified as takzir sanctions, namely improving the perpetrator's personality (special prevention), preventing others (general prevention) and repaying the perpetrator's crime (without removing sins), associated with The theory of Islamic punishment is based on the theory of al-Answer, namely penance for sins, this sanction does not erase the sins of the perpetrator. Castration can only be said to be a recompense for mere mistakes and the theory of al-zawajir: in terms of preventing, it includes the meaning of preventing others from doing the same thing. , this theory leads to the function of al-ta'dib (education) for perpetrators who will later convert them.